1999
DOI: 10.1159/000018275
|View full text |Cite
|
Sign up to set email alerts
|

Nevus comedonicus

Abstract: The nevus comedonicus (NC) is an uncommon variant of adnexal hamartoma which appears clinically as linear groups of open comedones. Its name may be a misnomer since, according to some, true comedones are not present. NC usually occurs by itself but may be linked with a variety of systemic findings such as skeletal or ocular anomalies. Although the nevus comedonicus is viewed by many as a hamartoma arising from a defective mesoderm, others consider this lesion to be an epidermal nevus involving the hair follicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 13 publications
(24 reference statements)
0
46
0
4
Order By: Relevance
“…141 Nevus comedonicus appears clinically as linear groups of open comedones presenting confluent clusters of dilated follicular orifices plugged with keratin. About 50% of cases are evident at birth, with the other 50% developing before the age of 10 years.…”
Section: Ser252trp-fgfr2-mutation and Comedogenesismentioning
confidence: 99%
“…141 Nevus comedonicus appears clinically as linear groups of open comedones presenting confluent clusters of dilated follicular orifices plugged with keratin. About 50% of cases are evident at birth, with the other 50% developing before the age of 10 years.…”
Section: Ser252trp-fgfr2-mutation and Comedogenesismentioning
confidence: 99%
“…Lesions may be extensive unilaterally [29]. NC has a predilection for the face, neck, trunk, and proximal extremities [31]. Inflammatory variants can occur, with recurrent pustules, cysts, and secondary bacterial infections.…”
Section: Nevus Comedonicusmentioning
confidence: 99%
“…Despite comedonelike appearance of the lesion, appearance of NC is not altered by hormonal variations, such as menarche, menopause, or pregnancy [35]. It has been hypothesized that NC arises from a developmental defect in the mesodermal component of the pilosebaceous unit, wherein the resulting follicular structure is only able to produce soft keratin, which then accumulates [31]. One study found increased filaggrin expression in closed comedones of NC but found no differences in cytokeratin expression between NC and normal skin [36].…”
Section: Nevus Comedonicusmentioning
confidence: 99%
See 2 more Smart Citations